Studying the effect of biological pollination and organic fertilization on some characteristics of yellow maize plants (Zea mays L.) (NTU Journal of Agriculture and Veterinary Science, 2025)
Sixteen samples of rhizosphere soil were collected for several plants from different locations, and phenotypic, microscopic, and biochemical tests were conducted on them. In this study, the two most efficient isolates were selected to study the effect of bioinoculation with nitrogen-fixing bacteria, Azotobacter chroococcum, and phosphate-dissolving bacteria, Bacillus subtilis, in the field experiment and two levels of organic fertilizer on Sheep waste body In two sites, the first in the fields of the College of Agriculture and Forestry with a clay texture, and the second site in the fields for the protection of crops with an alluvial mixed texture, regarding the growth and yield of yellow maize (Zea mays L.), the isolates used in the study were grown and preserved at a temperature of 4°C until used in the field. Use two levels of organic fertilizer (0% and 2%) and in two locations with different textures (clay and silty Loam). The chemical fertilizer N, P, and K were added to all treatments at one level according to the fertilizer recommendation, and then the seeds were planted after preparing them in the carrier.The study employed a randomized complete block design (RCBD) with three replications in the field, and the Duncan test was used to compare the means. The results of the study showed:The treatment inoculated with a mixture of chroococcum + B. subtilis and fertilized with sheep waste at the clay texture outperformed all treatments with regard to the characteristics (plant height, biological yield), and gave the highest values, reaching (323.667 cm and 19763.3 tons ha-1) on straight.The treatment inoculated with a mixture of chroococcum + B. subtilis excelled in the clay type, whether fertilized with organic fertilizer or not, as it gave the highest values ??for the character of the shoots of the plant (905,000 and 902,667 g).The treatment that was not inoculated and was not organically fertilized with the clay texture produced the highest percentage of oil, amounting to 6.331%, while the treatment that was inoculated with a mixture of A. chroococcum + B. subtilis fertilized with sheep waste in Silty Loam recorded the lowest percentage of oil, amounting to 4.025%.